The Chicano Feminist Identity and Cultural Conflict in Sanchez’s I’m Not The Perfect Mexican Daughter - Kasih, E. Ngestirosa Endang Woro; Wardaningsih, Agustin Diana; Putra, Ahmad Vahry Lilam (Pusat Studi Gender Universitas Jember, 2024)
This research delves into feminist themes within the novel